PENGARUH PENGGUNAAN MEDIA FERROFLUID DALAM PEMBELAJARAN MAGNET DAN MEDAN MAGNET TERHADAP PEMAHAMAN SISWA KELAS V - Afifatul Nur Azizah; Sudi Dul Aji; Farida Nur Kumala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the effect of using Ferrofluid media on the understanding of the concept of magnets and magnetic fields of fifth grade elementary school students. The background of this study is based on the low understanding of students towards abstract science material and the lack of use of innovative experimental media such as Ferrofluid in learning. This study uses a quantitative approach with a quasi-experimental design of the pretest and posttest control group design type. The subjects of this study consisted of 76 students of SDN 1 Dampit who were divided into experimental and control classes. The instrument was in the form of multiple-choice questions that were tested for validity and reliability. The data analysis technique in this study used prerequisite tests (normality and homogeneity tests) and hypothesis tests using independent sample t-tests. The results of this study showed that there was a significant difference between the posttest results of the experimental and control classes. The conclusion of this study is that the use of ferrofluid as an experimental medium has a positive impact on improving students' understanding of the concept of magnets and magnetic fields. The implication of this study is the importance of using experimental media based on concrete visualization in science learning in elementary schools.